A Review on Regenerative Braking System - Jeeva Bharathi, S.; Sri Hari Prasath, R.; Sriram, K.; Shankar, A. (International Journal of Psychosocial Rehabilitation, 2019)
In this review paper we present, Electric vehicles will be a necessary need for our use very soon. Today, in existing conventional braking technologies consumes a lot of energy during braking and as per the laws of physics (The energy can be neither created nor destroyed), while braking the heat energy converted for kinetic energy is dissipated into atmosphere. Therefore, regenerative braking is the most important method of conservation of energy. It increases the efficiency of electric vehicles by reducing waste of energy. In regenerative braking mode, the kinetic energy of the wheels is converted into electricity and stored in the battery or capacitor. Some existing systems are able to capture and store as much as 70% of energy. This method has been improved using flywheels, DC-DC converters, and super capacitors.